The Correlation Between Directed Writing Activities and Listening Skills Among Tenth-Grade Students at SMA Negeri 1 Angkola Selatan - Siregar, Parlindungan; Ramadhani, Yulia Rizki; Nasution, Leli Suryany (ETANIC Journal Of English Language Teaching And Applied Linguistics, 2023)
This research investigates the correlation between directed writing activities and students' listening skills among tenth-grade students at SMA Negeri 1 Angkola Selatan. English, as a global language, is crucial for communication and knowledge acquisition. However, many Indonesian students face challenges in mastering English, particularly in writing and listening. This study aims to explore whether directed writing activities can enhance students' listening skills, thereby improving overall language proficiency. The study employed a quantitative research method, collecting primary data through observations, interviews, and tests from 30 randomly selected students. The analysis utilized Pearson's product-moment correlation coefficient to determine the relationship between the variables. The results revealed a significant positive correlation (rxy = 0.645) between directed writing activities and listening skills, indicating that students who engaged in directed writing activities demonstrated improved listening skills. The findings suggest that incorporating directed writing activities in the English curriculum can effectively enhance students' listening abilities. This approach not only aids in developing writing skills but also reinforces listening, creating a more comprehensive language learning experience. The study recommends that educators adopt interactive and integrative teaching techniques to foster both writing and listening skills among students. The research concludes that directed writing activities significantly contribute to improving students' listening skills, emphasizing the need for innovative teaching strategies in English language education. Further studies are suggested to explore the impact of such activities on other language skills and in different educational settings to generalize the findings.